2015
DOI: 10.1039/c5ra04734j
|View full text |Cite
|
Sign up to set email alerts
|

Novel environment friendly inorganic red pigments based on Bi4V2O11

Abstract: Novel environment friendly inorganic red pigments, (Bi 1ÀxÀy Zr x Al y ) 4 V 2 O 11+d (0 # x # 0.15; 0 # y # 0.10), were successfully synthesized by a conventional solid state reaction method, and their colour properties were characterized. The colour of the obtained pigments was dependent on the calcination condition and the sample composition, and the highest red hue was obtained for the (Bi 0.92 Zr 0.07 Al 0.01 ) 4 V 2 O 11.34 pigment calcined at 800 C for 10 h in a flow of pure O 2 . The a* value correspon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 27 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…The changes in spectral shape after each resistance test are negligible. The color coordinate data were examined and the color difference (ΔE) was estimated from the color coordinate data before and after the examinations using the following equation 16 The color coordinate data of the samples before and after the heat, acid, and base resistant examinations are summarized in Table S5. ΔE values for after heat, acid, and base resistant examinations are 3.4, 4.1, and 4.3, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The changes in spectral shape after each resistance test are negligible. The color coordinate data were examined and the color difference (ΔE) was estimated from the color coordinate data before and after the examinations using the following equation 16 The color coordinate data of the samples before and after the heat, acid, and base resistant examinations are summarized in Table S5. ΔE values for after heat, acid, and base resistant examinations are 3.4, 4.1, and 4.3, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…C* and h values are also given. The undoped Bi 4 V 2 O 11 pigment and the BiTiVO, BiZrVO, and BiHf VO pigments showed relatively high 21) and b* values of 5 or less, and were low-saturation dark colors. The BiCuVO, BiMnVO, and BiCoVO had much lower C* (i.e., unvivid) and higher h (i.e., out of the red region).…”
Section: Color Characterization Of the Synthesized Pigmentsmentioning
confidence: 96%
“…Wendeus et al 21) examined Zr and Al-doped red pigments based on Bi 4 V 2 O 11 , and reported a relatively high redness (a* = 41.9) for (Bi 0.92 Zr 0.07 Al 0.01 ) 4 V 2 O 11.34 . They reported that the calcination in an oxygen atmosphere yielded a more reddish pigment.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] In particular, development of novel red pigments has been required and several studies have been reported. [18][19][20][21][22][23][24][25][26][27] Among them, it has been reported that Ca 1Àx La x TaO 2Àx N 1+x and Ce 2 S 3 showed bright red colour. 18,19 But, unfortunately, harmful NO x and SO x are generated when these nitride and sulphide pigments are incinerated.…”
Section: Introductionmentioning
confidence: 99%